Civil Society and Disarmament 2015 - United Nations Office for Disarmament Affairs (United Nations, 2016)
This publication contains the statements by representatives of civil society organizations which were delivered on 7 May 2015 during the Non-Governmental Organization segment of the 2015 Review Conference of the Treaty on the NonProliferation of Nuclear Weapons.